Comparative Assessment of the Effect of Ibuprofen and Etodolac on Edema, Trismus, and Pain in Lower Third Molar Surgery: A Randomized Clinical Trial - Silva de Oliveira, Júlio César [UNESP]; Grossi de Oliveira, Gustavo Augusto [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (Elsevier, 2016)
Purpose To compare the efficacy of ibuprofen (IBU) and etodolac (ETO) for controlling pain, edema, and trismus after extraction of lower third molars. Materials and Methods Twenty adolescents and adults with 2 impacted mandibular-third molars (in similar positions) were selected for the study. Patients were randomly assigned either to the IBU group (600 mg of IBU 3 times a day for 3 days) or to the ETO group (300 mg of ETO 3 times a day for 3 days). Drugs were administered immediately after dental extraction. Results During the first 2 days after extraction, swelling was more pronounced in the IBU group than in the ETO group (P = .033). Seven days after surgery, there was no difference in the degree of edema between the groups. At the 2- and 7-day evaluation points, mouth opening was significantly more reduced in the IBU group than in the ETO group (P < .05). After the first 6 hours, the ETO group had more effective pain relief (P < .05), but after this time point, both groups reported similar degrees of relief. Compared with the IBU group, the ETO group had a lower need for administration of additional rescue analgesics. Conclusions After extraction of impacted lower third molars, we found that swelling, trismus, and pain were more effectively controlled with ETO than with IBU.